Using Josiah Wedgwood to Teach the Industrial Revolution - Hall, Phyllis; Sprinkle, John (Teaching History: A Journal of Methods, 1991)
Freshman European history surveys can be deadly. Instructors must cover hundreds of years in one term. This time restriction requires a general treatment of significant periods, events, people, and trends. Continual doses of general information can kill student interest. Therefore, I try various means to put life into the broad treatment of material. I assign readings to give in-depth analysis of selected topics; I supplement my classes with slides, films, and videos providing visual expressions of the material; and I discuss my own research when it is relevant to the class. Sometimes I use the biography of a special person whose life illustrates a general period or theme of history. Such a person is Josiah Wedgwood (17301795), an innovative potter and an enterprising businessman, whose life touched on the main features of the industrial revolution in England.